Seroprevalence and detection of contagious bovine pleuropneumonia (CBPP) in northeast states of Peninsular Malaysia - M., Zarina; Saad, Mohd Zamri; Hassan, Latiffah; Salisi, Mohd Shahrom; O., Norlida (Universiti Putra Malaysia Press, 2016)
Contagious Bovine Pleuropneumonia (CBPP) is a highly infectious disease of cattle caused by Mycoplasma mycoides subsp. mycoides Small Colony (MmmSC). It is a disease recognised by OIE that needs to be controlled or eradicated through surveillance system. This study establishes the sero-prevalence of CBPP, as well as attempts to isolate and identify the agent of CBPP from cattle in Kelantan and Terengganu, the northeastern states of Peninsular Malaysia, where cattle movement was high. A total of 3,242 sera from 428 farms were processed between 2011 and 2014 using the competitive ELISA (c-ELISA). The animal-level prevalence ranged between 5% (46/917) in Terengganu and 9% (220/2325) in Kelantan, whereas the herd prevalence ranged between 12% (22/210) in Terengganu and 24% (53/218) in Kelantan. The overall animal-level prevalence was 8% (266/3242), while the herd prevalence was 17% (75/428). Two hundred and four nasal swabs from 18 positive herds in Kelantan and 163 lung and mediastinal lymph node samples were processed for isolation of MmmSc before confirmation by PCR and immunoperoxidase. Forty-one samples showed turbidity in PPLO broth and 15 lung and mediastinal lymph node samples had 'fried-egg colony' growth on the PPLO agar, which were suggestive of Mycoplasma infection. However, all were negative for MmmSC by PCR and immunoperoxidase. Thus, the northeastern part of Peninsular Malaysia remains positive serology for CBPP without isolation.